Dolly Parton : songteller, my life in lyrics - Parton, Dolly; Oermann, Robert K. (Chronicle Books, 2020)
"For the first time ever, legendary singer-songwriter Dolly Parton brings you behind the lyrics of 175 of her songs to reveal the personal stories and vibrant memories that have inspired sixty years of songwriting. Lushly illustrated and told in Dolly's inimitable voice, this rich collection offers an intimate, exclusive look at the colorful life, prolific career, and rags-to-rhinestones journey of one of the most revered entertainers of our time"--